The book of Ecclesiastes - Longman, Tremper (The New International Commentary on the Old Testament, 1998)
Cover -- Title Page -- Copyright Page -- Dedication -- Contents -- General Editor's Preface -- Author's Preface -- Abbreviations -- Introduction -- I. Title -- II. Authorship -- III. Excursus: Who was Qohelet? -- IV. Date -- V. Language -- VI. Genre -- VII. Structure -- VIII. Literary Style -- IX. Text -- X. Canon -- XI. Theological Message -- XII. Qohelet's Theology -- XIII. Theology of the book as a whole -- XIV. From a New Testament Perspective -- XV. Bibliography -- Text And Commentary -- I. Frame Narrative: Prologue (1:1-11) -- A. Superscription (1:1) -- B. Introduction to Qohelet's Thought (1:2-11) -- II. Qohelet's Autobiographical speech (1:12-12:7) -- A. Autobiographical Introduction (1:12) -- B. "Solomon's" Quest for the Meaning of Life (1:13-2:26) -- 1. Introductory Reflections -- 2. The Pursuit of Meaning in Pleasure (2:1-11) -- 3. Death Renders Both Wisdom and Folly Meaningless (2:12-17) -- 4. Death Renders Toil Meaningless (2:18-23) -- 5. Carpe Diem!-God Allows Some to Enjoy Life (2:24-26) -- C. The Quest Continues (3:1-6:9) -- 1. The Burden of the "Proper Time" (3:1-15) -- 2. Is There Any Justice? (3:16-22) -- 3. Better Off Dead (4:1-3) -- 4. Once Again-The Meaninglessness of Work (4:4-6) -- 5. Another Reflection on Meaninglessness: The Lonely Miser (4:7-8) -- 6. The Advantages of Companionship (4:9-12) -- 7. Political Power Is Meaningless: An Anecdote (4:13-16) -- 8. God Is in Heaven (4:17-5:6 [English 5:1-7]) -- 9. The Network of Oppression (5:7-8 [English 5:8-9]) -- 10. The Meaninglessness of Wealth (5:9-6:9 [English 5:10-6:9]) -- D. Qohelet's Wise Advice (6:10-12:7) -- 1. The Future-Determined and Unknown (6:10-12) -- 2. Miscellaneous Advice (7:1-14) -- 3. The Limitations of Human Wisdom and Righteousness (7:15-22) -- 4. Inaccessible Wisdom (7:23-24) -- 5. Seeking and (Not) Finding (7:25-29) -- 6. No One Is Like the Wise! (8:1)